The Role of the Aceh Truth and Reconciliation Commission in Efforts to Restore the Rights of Conflict Victims in Aceh - M. Luthfi Delfian; Chairul Fahmi; Muslem Muslem; Safinaz Mohd Hussein; Shafiyah Rahmah (al-Battar: Jurnal Pamungkas Hukum, 2026)
The armed conflict in Aceh for nearly three decades has had serious impacts on civil society, including family loss, psychological trauma, poverty, and limited access to justice. The establishment of the Aceh Truth and Reconciliation Commission (KKR) is an important effort in the framework of transitional justice to uncover the truth and restore victims' rights. However, the cancellation of Law Number 27 of 2004 concerning KKR by the Constitutional Court erased the basis of national law, thereby weakening the state's responsibility in the recovery of victims. This study aims to analyze the role of the Aceh KKR in restoring victims' rights and the impact of the repeal of the law on the effectiveness of recovery. This study uses an empirical-normative method with a legislative and sociological approach. Primary data were obtained through in-depth interviews with three families of conflict victims in Blang Bintang District, Aceh Besar, while secondary data came from academic literature, laws and regulations, and reports from human rights institutions. The analysis was carried out qualitatively to understand the relationship between the legal framework and the social reality of the victim. The results of the study show that the Aceh KKR carries out recovery through disclosure of the truth, reparation recommendations, and social reconciliation. However, the absence of national legal support creates legal uncertainty, administrative barriers, and psychological burdens for victims. Thus, the Aceh KKR plays an important but limited role in the national legal vacuum. Therefore, this study recommends strengthening the national legal framework that supports transitional justice as well as the implementation of effective and sustainable reparations for conflict victims.